IMPLEMENTASI METODE SMART DALAM SISTEM PENDUKUNG KEPUTUSAN PELANGGARAN TATA TERTIB SISWA - Setiaji, Ganang; Yulianti, Liza; Yupianti, Yupianti (UNIVED Press, 2022)
ABSTRACT: SMAN 4 Bengkulu City is a school that has many students in the Bengkulu City environment. SMA Negeri 4 Bengkulu City has several rules and regulations that must be obeyed by all students but not infrequently these rules and regulations are violated by some students. This study aims to design a decision support system for sanctions for violating student rules using the Simple Multi Attributte Rating Technique (SMART) method. The system that will be designed has several weighted assessment and summation criteria for each alternative on each attribute or existing violation criteria. Any violations committed by students can be processed quickly and accurately with predetermined sanctions and actions, have the same calculations between manual calculations and calculations on the system so that they can assist BK teachers in the reporting process to the principal at SMA Negeri 4 Bengkulu City. It is hoped that this application will be able to use this application in determining violations of rules and regulations in Bengkulu, as well as the maintenance of applications that the writer has previously made so that in the future it can be used by SMA Negeri 4 Bengkulu City. Keywords: Decision Support System, SMART, Violation of Rules.